IMPORTANCE OF TRANSPORT IN THE INTERNATIONAL ECONOMIC RELATIONS OF UZBEKISTAN IN THE CONDITIONS OF GLOBALIZATION - Umarali Gulmatov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is discussed joint efforts to develop the transport and transit potential of Central Asia and the development of measures in this regard. Taking into account the importance and urgency of developing Central Asia as a single region from the first days of his presidency, President Shavkat Mirziyoyev pursued an active regional policy, created a favorable political environment in Central Asia, and established constructive and mutually beneficial relations. In our country, special attention is paid to the further development of transport infrastructure and increasing the volume of transit traffic. It is known that Uzbekistan has long been known as a country on the Great Silk Road, which connects West and East. Today, this ancient road is being redesigned and connected nations. At present, the modernization and renewal of our country, the formation of a qualitatively new, modern structure of our economy, the integrated development of our regions are closely linked with the improvement of transport and communication systems. To address the above problems, strategic directions for the reform of the transport system have been identified and work has begun to create a single national transport system in the country. The development of all sectors of the industry - rail, road, air transport. Urgent tasks have been set to increase the competitiveness of roads and railways in Uzbekistan.